The interplay of ubiquitous DNA-binding factors, availability of binding sites in the chromatin, and DNA methylation in the differential regulation of phosphoenolpyruvate carboxykinase gene expression. - Faber, S (1991)
We have identified DNA elements in the phosphoenolpyruvate carboxykinase (PEPCK) gene promoter which are bound 'in vivo' by proteins under conditions of basal level gene expression and have evaluated several hypothesis to account for the tissue specific expression of the gene. In vitro DNase I footprinting demonstrated that factors which bind to basal expression elements of the PEPCK promoter, the BSE/CRE and NFI/CCAAT sites, are also present in HTC and XC cells which do not express the PEPCK gene. 'In vivo' DNase I footprinting demonstrated that the BSE/CRE, NFI/CCAAT, and three additional sites are bound by protein in H4IIE cells which express the PEPCK gene but not in the HTC or XC cells. No evidence for a repressor protein or for phased nucleosome binding to the PEPCK promoter in HTC or XC cells could be detected. Genomic sequencing was used to determine if differential methylation of the PEPCK promoter could account for the lack of factor binding in HTC and XC nuclei. None of the 14 cytosine residues in CpG dinucleotides was methylated in H4IIE or rat liver DNA, all were methylated in rat sperm DNA, and 6 were methylated in HTC DNA; including the cytosine at position--90 within the BSE/CRE. Only one cytosine residue, at position--90, was methylated in XC DNA. Treatment of XC cells with 5-azacytidine resulted in loss of methylation at the--90 position yet this was insufficient to allow synthesis of a detectable amount of PEPCK mRNA.